Canggah Coffee as the Processed Products of Micro Enterprises: System Design of E-Commerce - Rahayu, Slamet; Iqbal, Muhammad; Ferdian, Nurizzi Rifqi; Fathurahman, Ferdi (International Journal of Social Science and Business, 2021)
The current spread of the Covid-19 virus in Indonesia has had a major impact in every aspect, especially Micro, Small, and Medium Enterprises. One of them is the production of Canggah Coffee (Kopi Canggah) in Subang regency located in Cupunegara village. Since the presence of Covid-19 pandemic, sales of Canggah Coffee have started to decline due to the reduced number of visitors to buy these processed coffee products. Thus, to face this problem, State Polytechnic of Subang supported by Indonesia Bangkit Micro, Small, and Medium Enterprises program intended to assist the problem by designing an e-commerce system to expand the the promotion of Canggah Coffee. The system design is developed by System Development Life Cycle (SDLC) method. The system is built through 5 stages, namely survey / analysis, design, coding, testing, implementation and maintenance. Afterwards, the system was successfully designed and built, it is begun to be used by Canggah Coffee. This system can provide information and online product sales so that the customers can order and buy these processed coffee products from their home. Additionally, this system also facilitates periodic transaction reports which is very useful for this Micro, Small, and Medium Enterprises.